Pattern of coronary artery occlusion in patients undergoing coronary angiography at Birat Medical College Teaching Hospital - Shah, Prashant; Bista, Madhab; KC, Heera (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Coronary artery disease (CAD), is the leading cause of death globally. Among different diagnostic and treatment procedures, coronary angiography is considered the gold standard. Birat Medical College Teaching Hospital (BMCTH) is also providing cardiovascular services to people from eastern Nepal and from the neighboring country India. We aim to analyze the pattern of coronary artery occlusion in patients undergoing coronary angiography. Method: A hospital based observational cross-sectional study was conducted at BMCTH from 10 Sep 2022 to 10 Jan 2023. A total of 220 patients were enrolled by consecutive sampling techniques. Ethical approval was obtained from the Institutional Review Committee of BMCTH. Data was collected on baseline characteristics, risk factors, clinical presentation and degree of coronary artery occlusion. Collected data was entered in Microsoft Excel and analyzed by Statistical Package for Social Sciences version 23. Frequency, mean, percentage were calculated. Result: Nearly half (49.1%) patients had significant, 6(2.7%) had intermittent CAD and 14(6.4%) had non critical CAD. Three patients (1.4%) had left main coronary artery disease. Left anterior descending artery 66(30%) was the most commonly involved. Single vessel disease was present in most patients 49(22.27%). Double vessel disease 15(46.8%) and triple vessel disease was more common 14(51.8%) in above 65 y of age. Conclusion: The coronary angiography revealed presence of significant coronary artery disease and multiple vessel involvement with increasing age.